Severe Fatigue is Highly Prevalent in Patients with IPF or Sarcoidosis - Bloem, Ada E. M. (J Clin Med, 2020)
In patients with interstitial lung disease (ILD) next to dyspnea, fatigue is expected to be the most prevalent symptom. Surprisingly, the prevalence of severe fatigue has been scarcely studied in ILD patients and limited information on its associated factors is available. This study aimed to determine the prevalence of severe fatigue in patients with idiopathic pulmonary fibrosis (IPF) or pulmonary sarcoidosis and to identify the relationship between fatigue, patient characteristics, and clinical parameters. In this cross-sectional study, fatigue (checklist individual strength-fatigue (CIS-Fat)), demographics, lung function, dyspnea (modified-Medical Research Council (mMRC)), sleepiness (Epworth Sleepiness Scale), anxiety/depression (hospital anxiety and depression scale (HADS-A/HADS-D)), catastrophizing (fatigue catastrophizing scale (FCS)), functional activity impairment (respiratory illness quality-of-life (QoL-RIQ-Activity)), and health status (EuroQol five-dimensional descriptive system (EQ-5D-5L)) were assessed in outpatients with ILD. Mean CIS-Fat scores were 34.1 (SD ± 11.2) in 59 IPF patients and 40.0 (12.3) in 58 sarcoidosis patients. Severe fatigue (SD ± ≥36 points) was present in IPF patients (47.5%) and sarcoidosis (69%). In IPF, CIS-Fat correlated strongly (ρ > 0.5; p < 0.01) with FCS, QoL-RIQ-Activity, and EQ-5D-5L-Health and moderately (0.3 < ρ < 0.5; p < 0.01) with EQ-5D-5L-Index, mMRC, and HADS-D. In sarcoidosis, CIS-Fat correlated strongly with EQ-5D-5L-Health, QoL-RIQ-Activity, EQ-5D-5L-Index, HADS-D, and mMRC and moderately with FCS and hospitalization <12 months. Severe fatigue is highly prevalent in ILD patients and is associated with dyspnea, depression, catastrophizing, functional activity impairments, and QoL.